A mixed methods investigation of students' attitudes towards statistics and quantitative research methods: a focus on postgraduate psychology students at a South African university - Ngantweni, Xolelwa (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Many University programs offer a course in either basic or intermediate statistics as part of the degree requirements prior to graduation (McGrath, Ferns, Greiner, Wanamaker and Brown, 2015). These statistics or quantitative research methods courses are integral in helping students gain vital skills in analysing quantitative data. Research (Schau, Stevens, Dauphinee, and Del Vecchio, 1995) does however indicate that most students have a perfunctory disposition towards these courses. My study sought to particularly investigate attitudes towards statistics and quantitative research methods amongst a sample of 61 postgraduate Psychology students at Rhodes University undertaking a 'Quantitative Research Methods' course as part of their degree offering. A mixed methods approach was used to investigate students' attitudes towards statistics and quantitative research methods. The Survey of Attitudes Toward Statistics (SATS-36) (Schau, 2003) captured student's attitudes towards statistics using a Likert Scale instrument; whereas detailed qualitative interviews accentuated findings from the SATS-36. Key quantitative findings from the SATS-36 including students' perceptions of statistics being a difficult course as well as students having a low affect towards statistics are detailed. Key qualitative findings related to why students experience statistics anxiety such as students' (1) fear of failing statistics, (2) The late introduction of statistics in the Psychology curriculum, and (3) The role of educator/s in alleviating or promoting feelings of statistics anxiety are noted. The significance of these findings as well as the contributions of the study to the teaching and learning of statistics and quantitative research methods courses at Rhodes University are explored, in light of other studies on the topic of statistics anxiety and attitudes towards statistics/ quantitative research methods.
Keywords: Fetal alcohol spectrum disorders -- South Africa; Statistics; Psychology -- Research; College students -- South Africa -- Attitudes; Psychology -- Research -- South Africa